PERILAKU SOSIAL KERJASAMA SISWA DI SDN 1 TAMBARANGAN - Rezki Anita (JURNAL SOCIUS, 2014)
Based on the observation on the students of SD Negeri Tambarangan 1 showed that there was still low cooperation in various group activities.  The method used in this study was qualitative research method.  The results showed that the students had low cooperation in various group activities at school, including cleaning shift, group learning, and classroom organization.  This is due to: (1) lack of the cooperation spirit within the group, (2) the ambiguity and misunderstanding of each role in the group, (3) the students’ inability to utilize their creativity, (4) the existence of conflicts within the group, (5) students were more concerned with their personal interests, (6) lack of trust in the other group members, (7) less involvement, and (8) the absence of good group organization.Keywords: Cooperation, Group Activities